Studies towards the exploitation of sonochemically formed microelectrode arrays for the development of electrochemical sensors. - Gornall, Davinia D. (Cranfield University, 2004)
Microelectrodes offer a number of advantages for exploitation as electrochemical sensors such as imparting stir-independence to sensor responses and allowing lower limits of detection to be minimised. Microelectrode arrays offer an attractive route for increasing the current responses of microelectrodes, whilst still retaining their advantageous properties. Despite this, no commercial sensors, to date, have successfully employed microelectrode arrays, largely due to conventional fabrication routes proving too costly to be economically viable for the production of disposable sensing devices. Previous work carried out by this research group has described a novel and patented procedure for the fabrication of microelectrode arrays via the sonochemical ablation of insulating polymer films electrochemically deposited upon conductive surfaces. This format lends itself to mass fabrication due to the simplicity and inexpensiveness of the approach. This thesis describes work focussed towards the optimisation of each of the individual components involved in the formation of sonochemically fabricated microelectrode arrays. In particular, factors and techniques that may facilitate the commercial exploitation and mass fabrication of such arrays as generic sensing templates are described. Screen printed carbon has been investigated for its suitability as a host electrode. The comparative use of a number of possible activation methods to increase amperometric current responses at such electrodes is also described. Homogeneous poly(o-phenylenediamine) films of -40 nm thickness formed at the surfaces of screen printed carbon electrodes via the anodic electropolymerisation of o-phenylenediamine are shown to serve as effective diffusional barriers, thus insulating the underlying carbon electrodes. Microelectrode arrays formed by the sonochemical ablation of such films to expose microscopic areas of the underlying conductive substrates are seen to possess electrode element populations of -7.3 x 104 cm 2. Over 400 such sensors are shown to be able to be fabricated simultaneously with reproducibility of responses <4% relative standard deviation. Amperometric and cyclic voltammetric characterisations of the thus produced microelectrode arrays performed in model redox systems are shown to agree with accepted theoretical microelectrode behaviour, demonstrating sigmoidal shaped voltammograms, fluctuations in steady-state current responses of <10% with convection, scan rate independence and fast attainment (<20 seconds) of steady-state responses. Arrays of this type are also demonstrated to be suitable for exploitation within aqueous chlorine sensing devices, offering detection limits of <0.005 mg/l free chlorine, representing an order of magnitude lower than those obtainable via contemporary optical wet chemistry based approaches. In order to demonstrate further the applicability of this approach to the mass fabrication of disposable devices, methods for the deposition of a chemical modifying layer are also investigated, to avoid the need for additional reagents.